Analisis Perbandingan antara PP No. 99 Tahun 2012 dengan Permenkumham No. 07 Tahun 2022 Tentang Aturan atau Syarat Remisi terhadap Koruptor di Indonesia - Puspita, Ela; Fahudi, Fahudi; Rasmah, Rasmah (Lembaga Yasin AlSys, 2024)
Corruption has long been a serious problem in Indonesia. To fight corruption and enforce the law, the government has issued several regulations governing remission of corruptors. Two regulations that have had a significant impact in this regard are Presidential Regulation Number 99 of 2012 and Minister of Law and Human Rights Regulation Number 7 of 2022. To combat rampant corruption, the government has taken various steps, one of which is by implementing remission rules for corruptors. In this context, a comparative analysis between two important regulations is very relevant, namely Presidential Regulation Number 99 of 2012 and Regulation of the Minister of Law and Human Rights Number 7 of 2022 concerning Rules or Provisions for Remission of Corruptors in Indonesia. Through an objective and critical approach, this journal will present a comprehensive analysis regarding the comparison between the two regulations. In analyzing it, we will look at important aspects such as the criteria for remission recipients, the requirements that must be met, as well as the social and legal impacts of implementing these regulations. This study uses a normative juridical approach, which examines the problem based on the applicable laws and regulations regarding the rules or conditions for remission of corruptors in Indonesia. Increasing these conditions aims to provide stricter sanctions against perpetrators of corruption. This latest regulation provides stricter and stricter sanctions against corruptors, with additional requirements such as payment of fines and compensation, as well as recovery of assets obtained illegally. This is expected to provide a deterrent effect on perpetrators of corruption and strengthen law enforcement in Indonesia.